2006
DOI: 10.1086/510666
|View full text |Cite
|
Sign up to set email alerts
|

Order in the Chaos: Spin-up and Spin-down during the 2002 Outburst of SAX J1808.4-3658

Abstract: We present a timing analysis of the 2002 outburst of the accreting millisecond pulsar SAX J1808.4Ϫ3658. A study of the phase delays of the entire pulse profile shows a behavior that is surprising and difficult to interpret: superposed to a general trend, a big jump by about 0.2 in phase is visible, starting at day 14 after the beginning of the outburst. An analysis of the pulse profile indicates the presence of a significant first harmonic. Studying the fundamental and the first harmonic separately, we find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
113
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(138 citation statements)
references
References 13 publications
22
113
2
1
Order By: Relevance
“…The main type of phase shift is connected with so-called timing noise which appears as irregular pulsephase jumps on timescales from hours to months (e.g., Burderi et al 2006;Hartman et al 2008). The amplitude of pulse-phase offsets usually correlated with Xray flux (e.g., Papitto et al 2007;Reggio et al 2008;Patruno et al 2009a,b) though sudden strong jumps in phase are also observed (e.g., Burderi et al 2006;Hartman et al 2008Hartman et al , 2009). This phenomenon is not completely understood yet.…”
Section: Discussion Of Phase Shifts In Accreting Millisecond Pulsars mentioning
confidence: 99%
“…The main type of phase shift is connected with so-called timing noise which appears as irregular pulsephase jumps on timescales from hours to months (e.g., Burderi et al 2006;Hartman et al 2008). The amplitude of pulse-phase offsets usually correlated with Xray flux (e.g., Papitto et al 2007;Reggio et al 2008;Patruno et al 2009a,b) though sudden strong jumps in phase are also observed (e.g., Burderi et al 2006;Hartman et al 2008Hartman et al , 2009). This phenomenon is not completely understood yet.…”
Section: Discussion Of Phase Shifts In Accreting Millisecond Pulsars mentioning
confidence: 99%
“…For the second harmonic that is less affected by phase noise (Burderi et al 2006;Riggio et al 2008), we repeated the fitting procedure using these phase delays. In the constant spin frequency derivative case, we obtainedν = 1.45(16) × 10 −13 Hz s −1 with a χ 2 r = 1.74(238.5/137).…”
Section: Second Harmonicmentioning
confidence: 99%
“…In the case of SAX J1808.4-3658 the distance to the source is known and is about 3.5 kpc [11]; therefore we can check if also in this case there is a discrepancy between the mass accretion rate inferred from the timing results and the observed X-ray luminosity. We still find a discrepancy, but, in this case, the mass accretion rate inferred from timing is only a factor of 2 larger than the X-ray luminosity, since this is about 1 × 10 37 ergs/s (see [10]). The spin-down observed at the end of the outburst can be explained, for instance, by a threading of the accretion disk by the neutron star magnetic field outside the accretion radius.…”
Section: Sax J18084-3658mentioning
confidence: 58%
“…We have performed a timing analysis of the 2002 outburst, which lasted about 40 days from October 15 to November 26, one of the most extensively covered by RXTE observations (see details in [10]). In this case, the pulse profile shows the presence of a significant first harmonic, and we therefore studied both the phase delays of the fundamental and the phase delays of the harmonic as a function of time.…”
Section: Sax J18084-3658mentioning
confidence: 99%